Get With The Guidelines–Heart Failure Hospital Participation and Its Association With Guideline-Directed Medical Therapy and Outcomes - Aradhana Verma; Gregg C. Fonarow; Paul Heidenreich; Larry A. Allen; Andrew P. Ambrosy; Shun Kohsaka; Anubodh S. Varshney; Nicholas Brownwell; Jun Fan; Alexander T. Sandhu (Circulation: Heart Failure, 2026)
BACKGROUND: Despite strong evidence, adoption of guideline-directed medical therapy (GDMT) for heart failure with reduced ejection fraction remains suboptimal. The Get With The Guidelines–Heart Failure (GWTG-HF) program was designed to close gaps in care. We evaluated whether hospital participation in GWTG-HF was associated with greater GDMT intensity and improved outcomes. METHODS: We conducted a retrospective analysis (2013–2021) of Medicare beneficiaries with part A and part D hospitalized with heart failure with reduced ejection fraction. Using a multiple baseline time series design, we compared changes in GDMT and outcomes before and after GWTG-HF enrollment with hospitals that never participated. Coprimary outcomes were a 90-day postdischarge GDMT score under a parallel and nonparallel slopes model. Secondary outcomes included class-specific medication fills, achievement of ≥50% target doses, and 30-day, 90-day, and 1-year all-cause and HF readmission and mortality. Mortality and first HF readmission were also evaluated using Cox proportional hazards models. We adjusted for baseline hospital performance, patient characteristics, and temporal trends. RESULTS: Among 1274 863 Medicare beneficiaries hospitalized for heart failure with reduced ejection fraction, 53.5% were treated at hospitals that never participated in GWTG-HF and 9.6% at GWTG-HF hospitals. Unadjusted median GDMT scores increased from 3.0 in both groups to 4.0 in nonparticipating hospitals and 4.5 in GWTG-HF hospitals at 90 days ( P